Assessment of length of stay as a quality indicator in urgent and emergency care patient care: a literature review (Research, Society and Development, 2021)
User service protocols, guided by the principles of the Humanization Policy (PNH), brought to managers and users a new concept of care in the SUS, user satisfaction with the care provided, was considered a quality indicator. So all health services started to work with the PNH, also including urgent and emergency services. Discuss the assessment of waiting time as an indicator of quality of the emergency service, address implemented, correlate the findings with the reality of the service presented in the literature. Descriptive character, literature review, using articles from scientific journals in the health area, theses and dissertations, available in: SCIELO, LILACS, MEDLINE; in Portuguese, English and Spanish. Analyzed by the method of Bardin. In urgent and emergency care, emergency care, pre-hospital care and others; the guidelines to be followed are: accepting the demand for risk assessment, guaranteeing referenced access, increasing resoluteness, providing access to the hospital structure and safe transfer, if necessary. Waiting time in emergency cases is crucial for the patient's outcome and cannot be delayed, and can be mitigated through the application of organizational protocols. It is also noteworthy that all phases of the ACCR process must be followed, as failures at one point in the process can lead to outcomes such as overcrowding in the unit, worsening of clinical conditions of patients still in the waiting room and overload of professionals.